Transit Passage dan Keamanan Selat Strategis: Studi Perbandingan Selat Hormuz, Malaka dan Bab El-Mandeb - Silva Hasanah Agustin (Jurnal Hukum Lex Generalis, 2026)
This study examines the comparative implementation of the transit passage regime under the United Nations Convention on the Law of the Sea in the Strait of Hormuz, the Strait of Malacca and Bab el-Mandeb, as well as the legal and nonlegal factors affecting the effectiveness of the international strait governance. Using normative legal research with statutory, conceptual, comparative and lawin-context approaches, this study finds that the implementation of transit passage varies across regions. The Strait of Hormuz reflects a contestative model shaped by geopolitical rivalries, the Strait of Malacca demonstrates a cooperative model through institutionalized regional cooperation, while Bab el-Mandeb represents a fragile model due to non-state security threats. The effectiveness of strategic strait governance is therefore determined not only by the normative force of UNCLOS, but also by geopolitics, institutional capacity, regional cooperation and the nature of security threats. This study affirms that the effectiveness of international maritime law depends heavily on political and security contexts, requiring an integrative approach to ensure freedom of navigation and sustainable stability of international trade.